(3GdQLGds - (3GdMSf (B- (3hjbGd(B: (3GdMSjf (B- (3Hf jhSa GHf Ydj Hf GdeWgQ GdMdj, LeGd GdOjf,J (B726 (3g` s ((3eMeO Hf CNj eMeO Hf eMeO Hf CNj eMeO GdcGJH s)
(3ChdgG (B:s
(3GdMeO ddg habfi ddJNdi Yf GdMQcGJ GdOfjhjI hHYO aEfi deG fXQJ ai GUhd GdaJGhi GdefJgjI haQhYgG GdfXQjI s
(3BNQgG (B:s
(3GHf YUGe dg fhGOQ GNHQfG LeGYI Yf CHj GdeaVd Yf MejO Yf GHf YUGe Je GdcJGH hddg GdMeO hGdefg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeQcRjI (B(3/1044) s
Keywords: (3GdJGQjNs